Determinants of Off-Farm Labour Participation and Time Allocation: Double-Hurdle Results in the Case of Fiji. Issue 1 (June 2021) - Xing, Zhongwei; Gounder, Rukmani
This study analyses the determinants of off-farm labour participation decisions of the agricultural households in Fiji. The analysis of joint decision to participate and the amount of time allocated to work is undertaken by using the double-hurdle model based on the Household Income and Expenditure Survey 2008–2009. The results show that household head status, age, marital status, ethnicity and education influence off-farm participation decisions of the farm households. On the households' time allocation decisions towards off-farm income-generating activities, the family size, remittances, income and several types of agricultural outputs influence the labour supply decisions. These households and farm characteristics are important in creating better returns, reducing risks from land constraints and natural disasters, managing income and consumption uncertainties and providing quality farm inputs. The results highlight some important policy implications that would help address low agricultural productivity and render increased support for off-farm income earning activities.